Drying Halves Decomposition Rates in River Networks by Decreasing Decomposer Diversity - Rubén del Campo; Thibault Datry; Arnaud Foulquier; Naiara López‐Rojo; Loïc Chalmandrier; Zoltán Csabai; David Cunillera‐Montcusí; Amaia A. Rodeles; Francisco J. Peñas; Bálint Pernecker; Núria Bonada; José Barquín; et al. (Global Change Biology, 2026)
River drying is intensifying worldwide due to climate change and increasing water abstraction, with major consequences for riverine biodiversity and ecosystem functioning. In river networks, drying not only alters local environmental conditions but also disrupts hydrological connectivity, reshaping the movement of organisms and resources at the river network scale. Leaf litter decomposition—a key ecosystem function in freshwater systems—is particularly sensitive to changes in the structure of decomposer communities. We hypothesized that spatiotemporal patterns of drying regulate decomposition by altering the diversity and composition of detritivorous macroinvertebrates, bacteria and fungi. We combined data from six European river networks spanning a wide latitudinal gradient to assess how local drying intensity and regional hydrological connectivity affect decomposition through changes in these decomposer groups. We found that short drying events (≤ 6 dry days) reduced decomposition rates by up to 50% mainly mediated by changes in the composition and diversity of decomposer communities. Drying decreased the diversity of groups contributing to decomposition, shifting the control of this function from a balanced contribution of fungi, bacteria and detritivores in perennial rivers to dominance by dry‐tolerant but less efficient bacteria in drying rivers. These community shifts persisted for months after flow resumption, causing sustained reductions in decomposition also in flowing conditions. Regional hydrological connectivity alleviated these negative effects of local drying by facilitating the recovery of more efficient aquatic decomposers. However, this effect depended on the river network. In more arid networks, stronger fragmentation hindered the recovery of decomposer communities after flow resumption. Overall, our results evidence that spatiotemporal patterns of drying can regulate the linkages between community structure and ecosystem functioning in river networks. As drying events become more frequent and prolonged, shifts in decomposers' diversity are likely to alter carbon cycling and energy fluxes in freshwater ecosystems under global change.

Habitat use differences mediate population threat exposure in white sturgeon - Jonathan A. Walter; Gabriel P. Singer; Daniel C. Reuman; Scott F. Colborne; Lawrence W. Sheppard; Daniel R. O’Donnell; Nat Coombs; Erin E. Tracy; Myfanwy Johnston; Emily A. Miller; Anna E. Steel; John T. Kelly; et al. (Environmental Biology of Fishes, 2026)

Carbon dioxide emissions across contrasting urban freshwater ecosystems - Clara Romero González‐Quijano; Sonia Herrero Ortega; Ruben del Campo; Peter Casper; Tobias Goldhammer; Mark O. Gessner; Gabriel A. Singer (Limnology and Oceanography, 2025)
Carbon dioxide (CO 2 ) emissions from freshwaters represent a globally important carbon flux. However, CO 2 fluxes from urban waters remain poorly constrained, and challenges remain for reliable upscaling, partly because of the high diversity of urban aquatic ecosystems. Using floating chambers to measure fluxes instantaneously and monitor them over multiple days, we estimated CO 2 emissions at 31 sites (lakes, ponds, rivers and streams) across the city of Berlin in four seasons. We evaluated land cover, nutrient concentrations, dissolved organic matter (DOM) composition, and chlorophyll‐ a and micropollutant concentrations as potential drivers of CO 2 emissions. CO 2 fluxes from lakes and ponds averaged 0.41 g C m −2 d −1 (ranging from −0.45 to 3.38 across sites and methods), aligning with the results of previous studies. CO 2 fluxes from our urban rivers and streams averaging 0.78 g C m −2 d −1 (range from −0.13 to 7.32) were lower than typically reported for running waters, conceivably due to limited gas exchange in the channelized lowland systems. CO 2 fluxes were positively associated with DOM aromaticity, pointing to allochthonous inputs delivering resources for respiration, whether from (treated) wastewater or sealed urban surfaces. Fluxes were lower and more variable in settings favoring primary production, suggesting an impact of CO 2 drawdown. This condition coincided with a higher percentage of paved area. Extrapolation to the entire aquatic network of the city yielded an annual emission estimate of 8.8 Gg C‐CO 2 . An implication of this study is that urban lakes, ponds, rivers, and streams should be recognized as distinct systems when establishing large‐scale CO 2 emission budgets.

Skyglow increases cyanobacteria abundance and organic matter cycling in lakes - Jeremy Fonvielle; Lukas Thuile Bistarelli; Yile Tao; Jason N. Woodhouse; Tom Shatwell; Luis A. Villalba; Stella A. Berger; Christopher C.M. Kyba; Jens C. Nejstgaard; Andreas Jechow; Franziska Kupprat; Susanne Stephan; et al. (Water Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Niche partitioning in a periphyton metacommunity peaks at intermediate species richness in midsized rivers - Thomas Fuß; Lukas Thuile Bistarelli; Robert Ptacnik; Gabriel A. Singer (Ecology, 2025)
The trait‐based partitioning of species plays a critical role in biodiversity–ecosystem function relationships. This niche partitioning drives and depends on community structure, yet this link remains elusive in the context of a metacommunity, where local community assembly is dictated by regional dispersal alongside local environmental conditions. Hence, elucidating the coupling of niche partitioning and community structure needs spatially explicit studies. Such studies are particularly necessary in river networks, where local habitats are highly connected by unidirectional water flow in a spatially complex network structure and frequent disturbance makes community structure strongly dependent on recolonization. Here, we show that taxonomic turnover among periphyton communities colonizing deployed bricks (microhabitats) at multiple sampling sites (local habitats) in a river network came along with a turnover in traits. This niche partitioning showed a hump‐shaped relationship with richness of periphyton communities, which increased along river size. Our observations suggest downstream dispersal along the river network to increase the regional metacommunity pool, which then ensures local colonization by taxa possessing diverse traits allowing them to efficiently partition into environmentally different microhabitats. However, at the most downstream sites, the excessive dispersal of widespread generalists drove mass effects which inflated richness with taxa that co‐occupied several microhabitats and swamped niche partitioning. Further, efficient niche partitioning depended on communities rich in rare taxa, an indication for the importance of specialists. Alarmingly, richness and rare taxa declined with high phosphorus concentrations and conductivity, respectively, two environmental variables which potentially reflected anthropogenic activity.

Strong large‐scale structure–function coupling in benthic bacteria is mediated by algae in a geodiverse river network - Lukas Thuile Bistarelli; Thomas Fuß; Franziska Walther; Luca Zoccarato; Lauren Talluto; Anna M. Romaní; Hans‐Peter Grossart; Gabriel A. Singer (Limnology and Oceanography, 2024)
Benthic bacteria in stream ecosystems drive organic matter mineralization. However, knowledge on how this ecosystem function is driven by bacterial community composition in interaction with environmental conditions and organic matter resources is poor. This is especially true when considering the regional scale of river networks, at which environmental conditions vary in a scale‐dependent manner and are spatially structured due to asymmetrical water flow. Similarly, organic matter resources may have a terrestrial origin in remote headwaters or be sourced locally from algae living in close proximity to bacteria in benthic biofilms. We investigated benthic biofilm meta‐community structure and function across the > 6700 km 2 river network of the near‐natural Vjosa in Albania and Greece and found a strong control of the benthic algal community on bacterial community composition (13.4% of variability explained). In addition, bacterial community composition has linkages to water chemistry, which itself is strongly shaped by the diverse geology in the catchment, and to dispersal, shaping metacommunity structure as a neutral process. Notably, bacterial community composition explained the largest single fraction of variability (31.5%) in extracellular enzymatic activities, while there was no dependency of enzyme ratios on organic matter nor environmental conditions. Synergistic effects between bacteria and algae accounted for additional 47.3% of variability in heterotrophic functioning, emphasizing the importance of algal–bacterial interactions in benthic biofilms. Our findings shed new light on bacterial structure–function coupling highlighting the importance of algal–bacterial interactions at the river network scale.

Comparative stable isotope analyses of green sturgeon ( Acipenser medirostris ) and white sturgeon ( A. transmontanus ) in the San Francisco estuary - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Molly Webb; A. Peter Klimley (Journal of Fish Biology, 2024)
Green sturgeon ( Acipenser medirostris ) and white sturgeon ( A. transmontanus ) are closely related, sympatric species that inhabit the San Francisco estuary. Green sturgeon have a more marine life history but both species spawn in the Sacramento River and reside for some duration in San Francisco Bay. These sturgeons are of conservation concern, yet little is known about their dietary competition when they overlap in space and time. To examine evidence of dietary differentiation, we collected whole blood and blood plasma from 26 green sturgeon and 35 white sturgeon in San Francisco Bay. Using carbon and nitrogen stable isotope analyses, we compared their relative trophic levels and foraging locations along the freshwater to marine gradient. Sampling blood plasma and whole blood allowed comparison of dietary integration over shorter and longer time scales, respectively. Plasma and whole blood δ 13 C values confirmed green sturgeon had more marine dietary sources than white sturgeon. Plasma δ 15 N values revealed white sturgeon fed at lower trophic levels than green sturgeon recently, however, whole blood δ 15 N values demonstrated the two species fed at the same trophic level over longer time scales. Larger individuals of both species had higher δ 13 C values than smaller individuals, reflecting more marine food sources in adulthood. Length did not affect δ 15 N values of either species. Isotope analyses supported the more marine life history of green than white sturgeon and potentially highlight a temporary trophic differentiation of diet between species during and preceding the overlapping life stage in San Francisco Bay.

Exploring macroinvertebrate biodiversity in the dynamic southern Balkan stream network of the Vjosa using preservative-based DNA metabarcoding - Marie V. Brasseur; Jan Martini; Olivia Wilfling; Remo Wüthrich; Emil Birnstiel; Rebecca Oester; Vera M. A. Zizka; Gabriel Singer; Florian Leese; Simon Vitecek (Aquatic Sciences, 2023)
Reliable biodiversity data are crucial for environmental research and management. Unfortunately, data paucity prevails for many regions and organismal groups such as aquatic invertebrates. High-throughput DNA-based identification, in particular DNA metabarcoding, has accelerated biodiversity data generation. However, in the process of metabarcoding, specimens are usually destroyed, precluding later specimen-based analyses. Metabarcoding of DNA released into the preservative ethanol has been proposed as a non-destructive alternative, but proof-of-principle studies have yielded ambiguous results, reporting variance in detection probability for various taxa and methodological biases. In this study, we tested the performance of preservative-based metabarcoding of aquatic invertebrates in comparison to a standard morpho-taxonomic assessment based on samples from one of Europe’s last free-flowing rivers, the Vjosa. Multi-habitat samples were collected at 43 sites in two seasons and stored in ethanol, after fixation in formaldehyde for morpho-taxonomic analyses. Preservative-based DNA metabarcoding detected three times more taxa but failed to detect other taxa found using the standard method. In addition to incomplete reference data and primer bias that likely precluded the detection of specific taxa, preservative-based DNA metabarcoding cannot provide accurate abundance estimates. However, the metabarcoding data revealed distinct small-scale and large-scale community patterns in the Vjosa river network, which were also recovered by quantitative data of the standard approach. Overall, our results indicate that preservative-based metabarcoding provides important biodiversity data, which could be further improved by quantitative validation. The method is robust and reliable, even though samples were taken under harsh field-conditions and stored without cooling. Further, our results emphasise the need for reliable DNA barcoding reference libraries. Building those may be supported by preservative-based metabarcoding that maintains intact vouchers for subsequent specimen-based analyses.

Movement patterns of juvenile green sturgeon (Acipenser medirostris) in the San Francisco Bay Estuary - Michael J. Thomas; Andrew L. Rypel; Gabriel P. Singer; A. Peter Klimley; Matthew D. Pagel; Eric D. Chapman; Nann A. Fangue (Environmental Biology of Fishes, 2022)
Little is known about the distribution and ecology of juvenile green sturgeon throughout their range and specifically within California’s Central Valley and the San Francisco Bay Estuary. The objective of our study was to identify rearing movement patterns of juvenile green sturgeon and their interaction with Delta and Bay habitats. Acoustic biotelemetry was used to record juvenile movements and residence within different regions of this highly modified watershed. We document a diversity of movements exhibited by 31 acoustically tagged juvenile green sturgeon monitored over a 9-month period. The juvenile sturgeon either (1) remained in the Delta or moved (2) into the Carquinez Straits, (3) into San Pablo Bay, (4) into San Pablo Bay but returned to Delta, (5) through the estuary and likely left through the mouth of the bay, (6) or left the estuary only to return later. Spatiotemporal habitat quality varies within and between Delta and Bay habitats. Variation in water year and hydrologic connectivity are likely to influence habitat quality and quantity, and behaviors may be differentially optimized for fitness in response to environmental variation. Our results provide initial evidence supporting multiple behavioral movement patterns and a broad use of regional habitats for green sturgeon in the California Central Valley. This apparent behavioral diversity observed through movement patterns may ensure long-term success of all population segments over time in an extremely variable environment, ultimately supporting overall population stability (i.e., the portfolio effect). Enhanced conservation efforts may be needed to protect juvenile green sturgeon and the habitats they rely upon.

Correction to: Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Spatio-temporal distribution of Green Sturgeon (Acipenser medirostris) and White Sturgeon (A. transmontanus) in the San Francisco Estuary and Sacramento River, California - Emily A. Miller; Gabriel P. Singer; Matthew L. Peterson; Eric D. Chapman; Myfanwy E. Johnston; Michael J. Thomas; Ryan D. Battleson; Marty Gingras; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Contrasting the migratory behavior and stranding risk of White Sturgeon and Chinook Salmon in a modified floodplain of California - Myfanwy Johnston; Jared Frantzich; Matthew B. Espe; Pascale Goertler; Gabriel Singer; Ted Sommer; A. Peter Klimley (Environmental Biology of Fishes, 2020)

Historic drought influences outmigration dynamics of juvenile fall and spring-run Chinook Salmon - Gabriel P Singer; Eric D. Chapman; Arnold J. Ammann; A. Peter Klimley; Andrew L. Rypel; Nann A. Fangue (Environmental Biology of Fishes, 2020)

Methane emissions from contrasting urban freshwaters: Rates, drivers, and a whole‐city footprint - Sonia Herrero Ortega; Clara Romero González‐Quijano; Peter Casper; Gabriel A. Singer; Mark O. Gessner (Global Change Biology, 2019)
Global urbanization trends impose major alterations on surface waters. This includes impacts on ecosystem functioning that can involve feedbacks on climate through changes in rates of greenhouse gas emissions. The combination of high nutrient supply and shallow depth typical of urban freshwaters is particularly conducive to high rates of methane (CH 4 ) production and emission, suggesting a potentially important role in the global CH 4 cycle. However, there is a lack of comprehensive flux data from diverse urban water bodies, of information on the underlying drivers, and of estimates for whole cities. Based on measurements over four seasons in a total of 32 water bodies in the city of Berlin, Germany, we calculate the total CH 4 emission from various types of surface waters of a large city in temperate climate at 2.6 ± 1.7 Gg CH 4 /year. The average total emission was 219 ± 490 mg CH 4 m −2 day −1 . Water chemical variables were surprisingly poor predictors of total CH 4 emissions, and proxies of productivity and oxygen conditions had low explanatory power as well, suggesting a complex combination of factors governing CH 4 fluxes from urban surface waters. However, small water bodies (area 4 emissions from freshwaters in the world's growing cities, facilitating extrapolation of urban emissions to large areas, including at the global scale.

Spatiotemporal occurrence of green sturgeon at dredging and placement sites in the San Francisco estuary - Eric D. Chapman; Emily A. Miller; Gabriel P. Singer; Alex R. Hearn; Michael J. Thomas; William N. Brostoff; Peter E. LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2019)

Climate-Induced Changes in Spring Snowmelt Impact Ecosystem Metabolism and Carbon Fluxes in an Alpine Stream Network - Amber J. Ulseth; Enrico Bertuzzo; Gabriel A. Singer; Jakob Schelker; Tom J. Battin (Ecosystems, 2018)

Artificial light at night decreases biomass and alters community composition of benthic primary producers in a sub‐alpine stream - Maja Grubisic; Gabriel Singer; M. Cristina Bruno; Roy H. A. van Grunsven; Alessandro Manfrin; Michael T. Monaghan; Franz Hölker (Limnology and Oceanography, 2017)
Artificial light at night (ALAN) is recognized as a contributor to environmental change and a biodiversity threat on a global scale. Despite its widespread use and numerous potential ecological effects, few studies have investigated the impacts on aquatic ecosystems and primary producers. Light is a source of energy and information for benthic autotrophs that form the basis of food webs in clear, shallow waters. Artificial night‐time illumination may thus affect biomass and community composition of primary producers. We experimentally mimicked the light conditions of a light‐polluted area (approximately 20 lux, white LED) in streamside flumes on a sub‐alpine stream. We compared the biomass and community composition of periphyton grown under ALAN with periphyton grown under a natural light regime in two seasons using communities in early (up to 3 weeks) and later (4–6 weeks) developmental stages. In early periphyton, ALAN decreased the biomass of autotrophs in both spring (57% at 3 weeks) and autumn (43% at 2 weeks), decreased the proportion of cyanobacteria in spring (54%), and altered the proportion of diatoms in autumn (11% decrease at 2 weeks and 5% increase at 3 weeks). No effects of ALAN were observed for later periphyton. Further work is needed to test whether streams with frequent physical disturbances that reset the successional development of periphyton are more affected by ALAN than streams with more stable conditions. As periphyton is a fundamental component of stream ecosystems, the impact of ALAN might propagate to higher trophic levels and/or affect critical ecosystem functions.

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Movements of steelhead (Oncorhynchus mykiss) smolts migrating through the San Francisco Bay Estuary - Eric D Chapman; Alex R Hearn; Gabriel P Singer; William N Brostoff; Peter E LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2015)

Movements of out-migrating late-fall run Chinook salmon (Oncorhynchus tshawytscha) smolts through the San Francisco Bay Estuary - Alex R. Hearn; Eric D. Chapman; Gabriel P. Singer; William N. Brostoff; Peter E. LaCivita; A. Peter Klimley (Environmental Biology of Fishes, 2014)

Rare but active taxa contribute to community dynamics of benthic biofilms in glacier‐fed streams - Linda Wilhelm; Katharina Besemer; Christina Fasching; Tim Urich; Gabriel A. Singer; Christopher Quince; Tom J. Battin (Environmental Microbiology, 2014)
Summary Glaciers harbour diverse microorganisms, which upon ice melt can be released downstream. In glacier‐fed streams microorganisms can attach to stones or sediments to form benthic biofilms. We used 454‐pyrosequencing to explore the bulk (16 S rDNA ) and putatively active (16 S rRNA ) microbial communities of stone and sediment biofilms across 26 glacier‐fed streams. We found differences in community composition between bulk and active communities among streams and a stronger congruence between biofilm types. Relative abundances of rRNA and rDNA were positively correlated across different taxa and taxonomic levels, but at lower taxonomic levels, the higher abundance in either the active or the bulk communities became more apparent. Here, environmental variables played a minor role in structuring active communities. However, we found a large number of rare taxa with higher relative abundances in rRNA compared with rDNA . This suggests that rare taxa contribute disproportionately to microbial community dynamics in glacier‐fed streams. Our findings propose that high community turnover, where taxa repeatedly enter and leave the ‘seed bank’, contributes to the maintenance of microbial biodiversity in harsh ecosystems with continuous environmental perturbations, such as glacier‐fed streams.

Behavior, movements, and habitat use of adult green sturgeon, Acipenser medirostris, in the upper Sacramento River - Michael J. Thomas; Matthew L. Peterson; Eric D. Chapman; Alex R. Hearn; Gabriel P. Singer; Ryan D. Battleson; A. Peter Klimley (Environmental Biology of Fishes, 2014)

Interannual variation of reach specific migratory success for Sacramento River hatchery yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) - Gabriel P. Singer; Alex R. Hearn; Eric D. Chapman; Matthew L. Peterson; Peter E. LaCivita; William N. Brostoff; Allison Bremner; A. P. Klimley (Environmental Biology of Fishes, 2013)

The effects of environmental factors on the migratory movement patterns of Sacramento River yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) - Cyril J. Michel; Arnold J. Ammann; Eric D. Chapman; Philip T. Sandstrom; Heidi E. Fish; Michael J. Thomas; Gabriel P. Singer; Steven T. Lindley; A. Peter Klimley; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)

Diel movements of out-migrating Chinook salmon (Oncorhynchus tshawytscha) and steelhead trout (Oncorhynchus mykiss) smolts in the Sacramento/San Joaquin watershed - Eric D. Chapman; Alex R. Hearn; Cyril J. Michel; Arnold J. Ammann; Steven T. Lindley; Michael J. Thomas; Philip T. Sandstrom; Gabriel P. Singer; Matthew L. Peterson; R. Bruce MacFarlane; A. Peter Klimley (Environmental Biology of Fishes, 2013)